1990
DOI: 10.1136/adc.65.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve hypoplasia: associations and management.

Abstract: Since its first description optic nerve hypoplasia has been identified with increasing frequency, and a range of associated problems have been described. The major neurological and endocrine associations are well established, but those factors that predispose to the development of optic nerve hypoplasia remain unclear. To understand the aetiology of these problems better, and to formulate a management regime, we studied a consecutive series of 40 patients who were divided into three groups. Group 1 (n=24) had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 14 publications
3
26
0
Order By: Relevance
“…Interestingly, as reported in the literature [ 11,24] maternal age of mothers of our patients with SOD was generally low: while in one study more than half of the patients had been born to mothers less than 20 years of age, in our survey, maternal age was 23 years (median). In addition, problems in the perinatal and neonatal periods were reported frequently in our survey as well as in other series of SOD patients [24,33]. Almost one third of the patients in Margalith's series [24,25] had required resuscitation after birth, four of our patients had needed mechanical ventilation after birth.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, as reported in the literature [ 11,24] maternal age of mothers of our patients with SOD was generally low: while in one study more than half of the patients had been born to mothers less than 20 years of age, in our survey, maternal age was 23 years (median). In addition, problems in the perinatal and neonatal periods were reported frequently in our survey as well as in other series of SOD patients [24,33]. Almost one third of the patients in Margalith's series [24,25] had required resuscitation after birth, four of our patients had needed mechanical ventilation after birth.…”
Section: Discussionmentioning
confidence: 61%
“…In another series of 22 SOD patients, 5 had congenital hemiparesis [27]. In addition, delayed mental development has been described in many individual patients with SOD [6,18,26,27,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…The association of low maternal age with SOD is not consensus 3,15,16 . A revision study of 100 patients with ONH identified association with prematurity in 21%, fetal alcohol syndrome in 9%, maternal diabetes in 6% and endocrine abnormalities in 6% 17 .…”
mentioning
confidence: 99%
“…The electroencephalogram (ECG) is normal in half of the cases 19,21 . The anomalies vary from developmental delay to focal deficits, like epilepsy and hemiparesis 7,15,20 . About 60% of the patients with bilateral ONH have some kind of neurological disorder, but the prevalence of developmental delay, mental retardation, cerebral palsy and seizures is not a consensus according to different studies 17,22 .…”
mentioning
confidence: 99%
See 1 more Smart Citation